Advances in photodynamic therapy : basic, translational, and clinical - Hamblin, Michael R.; Mróz, Paweł (Artech House engineering in medicine & biology series., 2008)
This resource brings you the latest advances in photodynamic therapy and offers you a solid understanding of the design, delivery and dosimetry of the three basic ingredients of PDT-photosensitizers, light and oxygen. The book covers novel areas of mechanistic and innovative translational approaches.